The damages caused by wisents in forest environment of Bieszczady, according to foresters’ opinion (European Bison Conservation Newsletter, 2010)
The reintroduction of Lowland-Caucasian line of wisents into natural environment of Bieszczady, initiated in the 60ties of previous century, has brought about a considerable success. Currently in the wild, about 300 individuals live in two separate subpopulations. An increment of numbers at relatively small winter refuges (on average 2000 ha, according to kernel 50% analysis) created the pressure upon forest stands. First significant damages (above 20% of damaged trees) within the area of 9 ha were observed in Baligro´d Forestry in 1996. Since 2002 forest districts inhabited by wisents are performing annual inventories of damages in forest plantations and stands. According to the data from 2002 – 2009, damaged area varied from 131 to 570 ha. Significant damages were found at area from 1 to 57 ha and were observed only within the home range of western subpopulation counting then about 130 individuals. On average, in 2009 per one individual, significantly damaged was 0.38 ha. The analysis took into consideration the repeatability of damages, as an important factor for the future of the stand. For the quality of timber, the most important are damages due to bark stripping, allowing for the development of rot, as result of infestation with fungi. At present numbers of wisents in Bieszczady, no correlation was found between winter density of animals and the extent of damages. Spatial distribution of damages was not limited only to the area of winter refugees.The data from long term monitoring allowed for the delineation of winter and summer refuges for wisents of Bieszczady. Those data can be used for elaboration of new, wisent-friendly methods of forest management, and to minimize effects of wisents’ presence, including damages caused by those animals. At present the level of damages attributed to wisents at Bieszczady, can be defined as economically tolerable.
Keywords: European bison; damages to the forest; Bieszczady; forest management